RADA develops a one-stop-shop in Jamaica - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
RADA develops a "one stop shop", Jamaica Gleaner, May 2002 Jamaica´s Rural Agricultural Development Authority (RADA) is developing an agricultural business information system (ABIS) to provide thousands of stakeholders with data on cro